Changing Perceptions, Altered Reality : Pakistan's Economy under Musharraf, 1999-2006 - Burki, Shahid Javed (Karachi Oxford University Press, 2008)
This book examines the various sectors of the economy that could become the source for sustainable growth. Thoughtful public policy in the high potential areas could help the country join the ranks of Asia's rapidly growing economies
Include Index.
Burki examines the various sectors of the economy that could become the source for sustainable growth. Thoughtful public policy in the high potential areas could help the country join the ranks of Asia's rapidly growing economies.
Keywords: Pakistan -- Economic history -- Economic development -- Economic policy